Association of body fat percentage with diabetes in hypertensive adults of different genders: a cross-sectional study - Rao, Jingan; Ding, Congcong; Shi, Yumeng; Zhou, Wei; Yu, Chao; Wang, Tao; Zhu, Lingjuan; Huang, Xiao; Bao, Huihui; Cheng, Xiaoshu (Frontiers in Endocrinology, 2025)
BackgroundWhile numerous epidemiological studies on body fat and diabetes already exist, there remains a scarcity of evidence regarding gender differences within hypertensive populations. The aim of this study was to examine gender-specific differences in the association of body fat percentage (BFP) with diabetes.Methods and resultsThis cross-sectional study encompassed 14,228 hypertensive patients from the Chinese Hypertension Registry. An easily obtainable anthropometric parameter, Clínica University de Navarra-Body Adiposity Estimator (CUN-BAE) equation was used to calculate body fat percentage (BFP). Diabetes was defined as the self-report of a previous diagnosis of diabetes, fasting blood glucose ≥ 7.0mmol/l, and the use of antidiabetic agents. The average BFP was 24.5% in men and 37.0% in women. Multivariate logistic regression analysis revealed a dose-dependent relationship between BFP and the risk of diabetes in men (odds ratio [OR] 1.09, 95% CI 1.07, 1.11) and women (OR 1.06, 95% CI 1.04, 1.07) while considering BFP as a continuous variable. After taking BFP as the quartile across different genders, compared with Q1 group, the risk of diabetes in Q4 group increased 176% (OR 2.76, 95% CI 2.15, 3.55) in men and 66% (OR 1.66, 95% CI 1.36, 2.03) in women. Furthermore, the positive association was found to be more significant in men, whether BFP was considered a continuous variable (P for interaction = 0.016) or a categorical variable in quartiles (P for interaction = 0.008). In addition, the positive association between BFP and diabetes remained consistent across various subgroups.ConclusionBFP is positively associated with the increased risk of diabetes in hypertensive population, especially in men.